Analisis Perbandingan Metode Belajar Individualized Learning dan Cooperative Learning dalam Penerapan Model Blended Learning di Stiba Makassar dan JTIK UNM - Hartini Ramli; Andi Ashilla Khaerunnisa; Adithiya Pratama Idil; Alif Kurniawan; Ainun Zahra Adistia; Muhammad Alwi (Sakura Digital Nusantara, 2023)
A good learning process is learning that can make students learn to receive knowledge and experience with their own efforts. Therefore, as lecturers must be able to create classes with innovative and effective learning so that these learning outcomes are in accordance with their goals. In the individual learning method, students sometimes get bored learning because there are no friends to exchange ideas with. As for learning that is carried out in groups, it will certainly be easier to do it, but on the other hand sometimes other students do not want to do the task because they depend on other friends. Blended learning in group learning can be combined with assignments to make video explanations of the themes that have been given. This can make it easier for students to understand the material, so if they still don't understand the material, they can play back the video that has been made. In the use of the cooperative learning learning model, students will help each other and solve the problems that have been given. It is very often used by teachers to train students in solving problems. In this study using quantitative methods by disseminating from filling in questions related to individualist learning research and cooperative learning. Which ones are used more often and more efficiently applied in the learning process.